Genetically Modified Plants and Beyond - Sithole Niang, Idah (IntechOpen, 2022)
Genetically Modified Plants and Beyond takes a fresh look at methodologies used in developing crop plants, discusses genome editing, and interrogates the regulatory approaches that different countries are proposing to use to regulate genetically modified (GM) vs genome-edited crop plants. The book focuses on root and tuber crops, ginger, and industrial/oil seed crops. A chapter on the production of pharmaceuticals in plants is also included. Going beyond the usual debate, the book includes case studies from Africa on the adoption of GM crops.